KARAKTERISTIK RUMAH TANGGA PETANI BERLAHAN SEMPIT: STRUKTUR DAN STABILITAS PENDAPATAN DI WILAYAH BERBASIS LAHAN SAWAH TADAH HUJAN (Kasus di Propinsi Jawa Tengah dan Jawa Timur) - NURMANAF, A. ROZANY (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 3, No. 2 Juli 2003, 2012)
The aim of the study is to identify the structure and stability household income of small size land holding farmers in the region where rain fed is the basic. Information about household characteristics is collected included sources of income and several factors related to the low-income level and instability of income. The study show that non agricultural income activity is the important source of household income, especially of small size land holding farmers who live in the rain fed (paddy field) area. Agricultural sector activities are dominance in the location, which has bad accessibility; but non-agricultural sector activities are dominance in the location with good accessibility. Level of income is higher in the low land area with good accessibility, which supported by higher productivity of production factor. Household income in high land area is more fluctuate because most of their income came from seasonal activities. On the other hand, in low land area, household income more stables because most of their income came from regular income in short period of time. Thus, the application of program in the future should be oriented not only in increasing household income but increasing income stability as well.
Keywords: Small size land holding farmer, rain fed, household income, income structure, income stability, physical accessibility